Quantifying Nectar Secretion Potential of Hygrophila auriculata (Schum.), Heine (Acanthaceae), and Salvia leucantha Cav. (Lamiaceae) for Honey Production - Tura Bareke; Admassu Addi (Advances in Agriculture)
The study was conducted to quantify the nectar secretion dynamics, and honey production capacity of Hygrophila auriculata and Salvia leucantha. One day before nectar collection, a group of flowers was enclosed with mesh bags to measure accumulated nectar volume. Moreover, nectar volume, concentration, temperature, and humidity were measured at intervals of 3 hours. The collected data was analysed using One-way ANOVA and linear regression. Nectar secretion dynamics of the two species were significantly varied (at p<0.05) at different times of the day. The nectar volume that became available between the two consecutive measurements (three-h intervals) varied from 1.5 to 2.5 μl/flower, and 4.1 to 5.5 μl/flower for H. auriculata and S. leucantha, respectively. The temperature was positively correlated with the nectar concentration for both species. However, the temperature was negatively correlated with the nectar volume of H. auriculata whereas almost at equilibrium for S. leucantha. Humidity was negatively correlated with nectar concentration for both species whereas it is positively correlated with nectar volume for H. auriculata. However, the relationships between humidity and nectar volume were almost found at equilibrium for S. leucantha. Based on the mean amount of nectar sugar secreted by the plants, the mean honey production potentials of the species were estimated to be 29.88 kg and 60.2 kg/ha depending on the size of the plants for H. auriculata and S. leucantha, respectively. Therefore, propagation and in-situ conservation of these species are also recommended for sustainable honey production.